Efficacy and safety of ziltivekimab in patients with chronic kidney disease susceptible to inflammatory diseases: a systematic review and meta-analysis of randomized controlled trials - Amr Elrosasy; Dalal Sabbagh; Mohammad Assaf; Husam Tarakhan; Ahmad Afyouni; Marwa O. Elgendy; Lamiaa N. Abdelaty; Refaat H. Omar; Ahmed Hamdy Zabady (SpringerOpen, 2024)
Abstract Background Patients with chronic kidney disease (CKD) are at risk of developing conditions such as atherosclerosis and inflammation-induced anemia (AI) due to persistent inflammation. Ziltivekimab, an antibody targeting interleukin-6, is being studied for its potential to reduce inflammatory markers in these patients. Methods Following PRISMA guidelines, we searched for relevant randomized controlled trials (RCTs) up to August 20, 2023, and analyzed the data using RevMan 5.4 software. The study period spanned from February 18, 2023, to September 23, 2023. We assessed efficacy outcomes such as high-sensitivity C-reactive protein (hs-CRP), serum amyloid A (SAA), and both high-density lipoprotein (HDL) and low-density lipoprotein (LDL), as well as safety outcomes, including adverse events (AEs) and infections. Pooled results were calculated using the random effects model and inverse variance method, with mean differences (MD) and risk ratios (RR) presented alongside 95% confidence intervals (CI). Results Our review included three RCTs with a total of 473 patients. Compared to the placebo group, patients treated with ziltivekimab showed significantly lower levels of hs-CRP, fibrinogen, and SAA (MD = − 51.64, 95% CI [− 73.73 to − 29.56], P < 0.00001; MD = − 48.23, 95% CI [− 61.73 to − 34.72], P < 0.00001; MD = − 26.34, 95% CI [− 38.63 to − 14.04], P < 0.0001, respectively). There was a notable increase in LDL and HDL levels (MD = 5.92, 95% CI [2.53 to 9.31], P = 0.0006, I2 = 0%; MD = − 5.73, 95% CI [3.75 to 7.71], P < 0.00001, I2 = 0%, respectively). No significant difference in AEs or infections was observed between the two groups. Meta-regression analysis indicated a significant linear relationship between the dose of ziltivekimab and its  effect on hs-CRP levels. Conclusion Ziltivekimab showed promise in significantly lowering inflammatory markers without a significant impact on AEs or infections, positioning it as a valuable treatment option for patients with chronic kidney disease CKD who are susceptible to inflammatory diseases, particularly atherosclerosis and autoimmune conditions.